Role of epigenetic modification in interferon treatment of hepatitis B virus infection - Yang, Zhijing; Sun, Baozhen; Xiang, Jingcheng; Wu, Han; Kan, Shaoning; Hao, Ming; Chang, Lu; Liu, Huimin; Wang, Dongxu; Liu, Weiwei (Frontiers in Immunology, 2022)
Human hepatitis B virus (HBV) is a small enveloped DNA virus that causes acute and chronic hepatitis. Chronic hepatitis B (CHB) is associated with hepatocellular carcinoma pathogenesis. Interferons (IFNs) have been used for the treatment of CHB for a long time, with advantages including less treatment duration and sustained virological response. Presently, various evidence suggests that epigenetic modification of the viral covalently closed circular DNA (cccDNA) and the host genome is crucial for the regulation of viral activity. This modification includes histone acetylation, DNA methylation, N6-methyladenosine, and non-coding RNA modification. IFN treatment for CHB can stimulate multiple IFN-stimulated genes for inhibiting virus replication. IFNs can also affect the HBV life cycle through epigenetic modulation. In this review, we summarized the different mechanisms through which IFN-α inhibits HBV replication, including epigenetic regulation. Moreover, the mechanisms underlying IFN activity are discussed, which indicated its potential as a novel treatment for CHB. It is proposed that epigenetic changes such as histone acetylation, DNA methylation, m6A methylation could be the targets of IFN, which may offer a novel approach to HBV treatment.